Empowering Research Ecosystems: Profiles and Bibliometrics Analysis of Research Officers at Universiti Malaya - Mohd Sarjidan, Mohd Arif; Abu Bakar, Azizi; Ismail, Noor Hidayati; Nordin, Noreena (Journal of Research Management and Governance, 2024)
The future trajectory of Universiti Malaya (UM) as a prominent regional research institution in Malaysia is intricately intertwined with the expertise and contributions of its research workforce, including the Research Officers (ROs). Given the pivotal role played by ROs in UM's research and innovation landscape, this paper briefly highlights an overview of their general roles in empowering UM's research and innovation landscape. The UM's ROs were profiled according to their gender, educational background, position, and grade. The study employs bibliometric analysis using data from the Scopus database to examine the scholarly output of ROs, focusing on their H-index, research fields, and the number of scientific publications produced between 2018 and 2022. The bibliometric impact analysis was performed by focusing on the citation of the publications, joint-publications network, and correlation of publications' contribution between the ROs over all the researchers in UM. The profile analysis indicates that ROs in UM are dominated by females, with postgraduate education qualification, and mostly holding entry-level positions (grade 41). The impact analysis shows that UM's ROs had an international network with 27% of their publications being jointly authored with international collaborators. They consistently contribute dto scholarly output by showing a coherent trend with the overall publication of UM. This work highlights the significant role of ROs in a Malaysian research university, setting the benchmark for other national universities in enhancing the credibility of ROs in achieving research and innovation excellence.